(untitled) (Research, Society and Development, 2026)
Dental caries remains one of the most prevalent chronic diseases in childhood, multifactorial and strongly influenced by inadequate dietary habits. This study aimed to examine the relationship between dietary habits and caries prevalence in early childhood (0-6 years), emphasizing nutrition, health education, and prevention. The narrative review identified that frequent intake of free sugars and ultra-processed foods, particularly between meals and at night, promotes oral microbiota imbalance, biofilm accumulation, and increased risk of carious lesions, with an odds ratio of 1.59 in recent meta-analyses. In Brazil, despite progress, 46.83% of 5-year-old children have caries experience (mean dmft = 2.14) and 41.2% have untreated caries, with marked regional and socioeconomic disparities (SB Brasil 2023). Protective factors include balanced diets, exclusive breastfeeding, proper oral hygiene, and fluoride use. Socioeconomic, cultural, and behavioral aspects significantly modulate dietary and oral care practices. Interdisciplinary integration between dentistry and nutrition, with early guidance for caregivers and public policies, is crucial to reduce prevalence and promote comprehensive children’s oral health.